Sales Forecasting Applications For Retail Companies Using Double Exponential Smoothing And Golden Section Methods - I Made Dwi Putra Asana; I Made Deni Kurniadi; Sugihya Artha Dwipayani; Ketut Jaya Atmaja (Institute of Computer Science (IOCS), 2022)
The availability of goods becomes one of the keys to the success of supermarket business in fulfilling consumer needs. The Forecasting methods can help to predict the sales in the future and it can help to find sales statistics daily, monthly or yearly. The application of exponential smoothing requires the process of determining the smoothing value by performing several tests. The determination of smoothing is a challenge in the forecasting process because it takes several tests of the optimal smoothing value to reduce forecasting errors. This study proposed the application of the golden section in optimizing the determination of the smoothing value. Golden section is an optimization method that provides extreme values ??of a non-linear function by reducing the range of values ??that contain extreme values. The results of the Forecasting method were based on the training data in which the trend and the result of the forecasting approached to the training data that used for forecasting. According to the results of the forecasting which conducted based on the training data was MAPE 26.460474 % and MAPE results from comparison of testing data obtained was 21.89696%.